Adverse events related to the use of enteral nutritional therapy - Anamarta Sbeghen Cervo; Tânia Solange Bosi de Souza Magnago; Jéssica Baldissera Carollo; Bruna Pereira Chagas; Adriano Silva de Oliveira; Janete de Souza Urbanetto
Aimed at verifying the occurrence of adverse events related to enteral nutrition use in patients of a public hospital in the countryside of Rio Grande do Sul. A quantitative, longitudinal and descriptive study, conducted in January-May 2012, that accompanied 46 patients admitted to the Intensive Care Unit and Medical Clinic. For evaluating the adverse events, we used quality indicators: inadvertent exit, tube obstruction and volume of infused diet. For analysis, we used descriptive statistics. The results showed that inadvertent exit of the tube and obstruction presented incidence rates of 4.6% and 2.1%, respectively. The volume of diet infused was less than that prescribed, due to pauses for body hygiene, tests and procedures, nausea / vomiting and delay in the availability of installation of the bottle in the unit. We conclude that the use of quality indicators in the assessment of care can help reduce damage to the patient.